Evaluation of Thermal Load and Optimization of Energy Requirements for Air Conditioning - Wiyogo Wiyogo; Harie Satiyadi Jaya; Vontas Alfenny Nahan; Galfri Siswandi; Jhonni Rentas Duling (Jurnal Informasi dan Teknologi, 2024)
This study evaluates air conditioning systems, focusing on addressing two primary types of heat: sensible and latent heat. Sensible heat, which affects temperature without causing a phase change in the material, is the main contributor to the cooling load and originates from human bodies, electronic equipment, and solar radiation penetrating windows. The study identifies that solar radiation significantly contributes to the heat load, particularly from the North and south sides. Peak heat gain on the north side occurs between 11:00 and 13:00, reaching 285,956 kcal/h, while the south side experiences reduced heat load due to natural shading. Meanwhile, latent heat, which relates to phase changes without a temperature increase, plays a minor role in this context. Heat gain from walls, particularly the east wall in Machine Classroom 1, reaching 5263 kcal/h at midnight, also plays a crucial part. Human activity, with a total of 7920 W or 7.92 kJ/h, and electronic equipment, contributing 32.55 watts or 117.18 kJ/h, add to the overall heat load. The total heat load peaks at midnight, with values around 44.235 kJ/h in Room 1 and 38.972 kJ/h in Room 2. Based on these calculations, the required AC capacity is 42,000 BTU/h for Room 1 and 36,000 BTU/h for Room 2. The capacity conversion shows a need for approximately 12.28 kW for Room 1 and 10.82 kW for Room 2. This study underscores the importance of selecting the appropriate AC capacity based on total heat load calculations involving various factors, especially in tropical regions like Palangka Raya, to ensure efficiency and thermal comfort.